Oxygen uptake kinetics and exercise capacity in children with cystic fibrosis. Issue 7 (2nd April 2015) - Fielding, Jeremy; Brantley, Lucy; Seigler, Nichole; McKie, Katie T.; Davison, Gareth W.; Harris, Ryan A
SUMMARY Exercise capacity, an objective measure of exercise intolerance, is known to predict quality of life and mortality in cystic fibrosis (CF). The mechanisms for exercise intolerance in patients with cystic fibrosis (CF), however, have yet to be fully elucidated. Accordingly, this study sought to investigate oxygen uptake kinetics and the impact of fat‐free mass (FFM) on exercise capacity in young patients with CF. 16 young patients with CF (age 13 ± 4 years; 10 female) and 15 matched controls (age 14 ± 3 years; nine female) participated. Pulmonary function and a maximal exercise test on a cycle ergometer using the Godfrey protocol were performed. Exercise capacity (VO2peak), VO2 response time (VO2RT), and functional VO2 gain (ΔVO2/ΔWR) were all determined. Lung function was the only demographic parameter significantly lower (P < 0.05) in CF compared to controls. Exercise capacity was lower in CF (P < 0.014) only when VO2 peak was normalized for FFM (43.5 ± 7.7 vs. 50.6 ± 7.4 ml/kg‐FFM/min) or expressed as % predicted (70.1 ± 14.3 vs. 85.4 ± 16.0%). The VO2RT was slower (36.1 ± 15.1 vs. 25.0 ± 12.4 sec; P = 0.03) and the ΔVO2/ΔWR slope was lower (8.4 ± 3 ml/min/watt vs. 10.1 ± 1.4 ml/min/watt; P = 0.02) in patients compared to controls, respectively. In conclusion, a delayed VO2 response time coupled with the lower functional VO2 gain (ΔVO2/ΔWR) suggest that young patients with CF have impairment in oxygen transport and oxygen utilization by the muscles. These data in addition to differences in VO2 peak normalized for FFM provide some insight that muscle mass and muscle metabolism contribute to exercise intolerance in CF. Pediatr Pulmonol. 2015; 50:647–654. © 2015 Wiley Periodicals, Inc.